Ethnic identity and self-esteem of aetas in Cati-Cati community in Jordan, Guimaras - Camit, Kristina L
This study aimed to know the socio-demograhic characteristics, ethnic identity, and self-esteem of Aetas in Cati-Cati community in Jordan, Guimaras. The study hypothesized that 1)Aetas have negative ethnic identity, 2)Aetas have high self-esteem, an 3)there is a direct relationship between the ethnic identity and self-esteem of the Aetas., Seventeen (17) males and forty-three (43) females were conveniently selected to participate in the study. They were the permanent residents of sito Cati-Cati in Barangay San Miguel, Jordan, Guimaras with ages ranging from sixteen (16) and above. Socio-demographic Questionnaire, Luhtanen and Crocker Ethnic Identity Scale, and Rosenberg Self-esteem Scale were the instrument utilized in conducting the in-depth individual interviews. The data were analyzed and interpreted using frequency, summation, and mean. Pearson r was used in computingfor the correlation between the two variables. Results revealed that most of the respondents were female pure Aetas with ages varying twenty-five (25) to forty-five (45) years. Generally, Aetas scored high in both in ethnic identity (79.57) and self-esteem (26.35) measures. This signified that education has refined the lifestyles of Aetas and has raised their perspectives towards themselves and their ethnic group. Despite achieving the social acceptance within the mainstream society, still some of the Aetas feel inevitably discriminated. Basically, because they are stereotyped to be similar with the mendicant Aetas found on the city streets. Therefore, the study concluded that majority of the Aetas have positive ethnic identity and high self-esteem. The Pearson r computations (r=0.262) implied that there exists a direct relationship between the ethnic identity and self-esteem of the Aetas in Cati-Cati community in Jordan, Guimaras.